Діалектний текст як джерело регіональних словників - Мартинова, Ганна; Щербина, Тетяна (Gwary Dziś, 2022)
The article states that in early 21st century, Slavic linguistics lexicographic arrangement of the dialect appeared to preserve the original lexical stock shaped through a national outlook and mentality, as well as cultural values of the creative Ukrainian nation. The article is aimed to represent the dialect stock of the Ukrainian lexicography in the early 21st century, as well as to stress the importance of a dialect text as a source for arranging a regional dictionary. That has accentuated the dialect text proper as a source for arranging a regional dictionary that includes specially represented patois lexical units, their registration according to the dialects and their expansion in the area under consideration. The approach enables a detailed description of the status quo, its peculiar features represented in the differentiated names, as well as peculiar stressed forms, regular and sporadic shifts in vowels and consonants in the registered lexical units. In spontaneous speech, lexical meanings are more complete and more objectively revealed, being largely enforced by new meanings in microtexts. The authors have proved that arranging dictionaries by meaningful texts complete reveals the registered units, as well as regional and local ones in spontaneous speech in various word-building, phonetic and grammatical variants in the dialect aspect. Broad comments provided for the entries are taken from dialect texts and ensure progress to a next narrative fragment promoting a way to learning other linguistic units characteristic of dialects. The dictionary grows into a hypertext, leading the reader from one registered unit to another, providing ethnic linguistic information while revealing a specific status quo interpreted by dialect speakers.